Distribution of Quinolones, Sulfonamides, Tetracyclines in Aquatic Environment and Antibiotic Resistance in Indochina - Suzuki, Satoru; Hoa, Phan Thi Phuong (Frontiers in Microbiology, 2012)
Southeast Asia has become the center of rapid industrial development and economic growth. However, this growth has far outpaced investment in public infrastructure, leading to the unregulated release of many pollutants, including wastewater-related contaminants such as antibiotics. Antibiotics are of major concern because they can easily be released into the environment from numerous sources, and can subsequently induce development of antibiotic-resistant bacteria. Recent studies have shown that for some categories of drugs this source-to-environment antibiotic resistance relationship is more complex. This review summarizes current understanding regarding the presence of quinolones, sulfonamides, and tetracyclines in aquatic environments of Indochina and the prevalence of bacteria resistant to them. Several noteworthy findings are discussed: 1) quinolone contamination and the occurrence of quinolone resistance are not correlated; 2) occurrence of the sul sulfonamide resistance gene varies geographically; and 3) microbial diversity might be related to the rate of oxytetracycline resistance.